Enhancing Teachers Proficiency with Digital Interactive Learning Resources for Differentiated Instruction - Yahya, Yahya; Febriana Sesunan, Mira; Syamsiyah, Nur; Asbanu, Husen; Pratama, Juan; Nur Afifa, Linda; Darsono (Fakultas Teknik Universitas Darma Persada, 2025)
The course seeks to enhance educators' competencies in creating customized learning experiences with digital interactive technologies, namely platforms like Wordwall and Quizizz. The event occurred on February 11, 2025, in the Bekasi region, involving high school and vocational school educators. The training materials encompassed the concept of diversified learning, an introduction to the Wordwall and Quizizz platforms, and exercises for developing interactive media that align with suitable teaching methodologies. The activity's outcomes demonstrated a notable enhancement in instructors' competencies in the creative and contextual utilization of digital media, alongside heightened understanding of the need of adaptive learning services tailored to student needs. This initiative enhances the transformation of digital education at the secondary school level.